Exploration of different quantitative polymerase chain reaction-based genotyping methods to distinguish Apcmin/+ mice from wildtype mice - Yuting Sun; Tingyu Zhou; Silin Ye; Effie Yin Tung Lau; Yao Zeng; Jessie Qiaoyi Liang (PLoS ONE, 2025)
Various molecular methods have been established for genotyping single-nucleotide variants (SNVs). However, despite the widespread availability of quantitative polymerase chain reaction (qPCR) instruments in biomedical laboratories, the lack of professional analytical tools impedes the application of qPCR in genotyping. Apcmin/+ mice, which harbour a germline Apc mutation (g.2549T>A) associated with multiple intestinal neoplasms, are extensively employed in colorectal cancer research. In this study, we used Apc as a model and assessed the feasibility of different qPCR-based methods for SNV genotyping, considering approaches with and without genotyping analytical tools. We initially employed allele-specific PCR followed by electrophoresis to determine the genotypes of Apc in tail tissues from potential Apcmin/+ mice, and this method served as the benchmark for evaluating the performance of qPCR-based methods. Dye-based qPCR and melting curve assays exhibited distinct dissociation patterns that differentiated between synthesised wildtype (TT) and heterozygous mutant (TA) DNA and between TT and TA genotype mice based on analysis of tissue samples. This discrimination ability of these assays was unaffected by the use of different intercalating dyes (SYBR Green I or EvaGreen). Dual-probe qPCR assays were developed to simultaneously detect mutant and wildtype alleles using differently labelled probes. The genotyping module and delta cycle threshold method were used to facilitate the analysis of results. The qPCR-based methods displayed 100% agreement with the standard genotyping outcomes. When the PCR–electrophoresis method was used, approximately 15% of the samples required re-examination to obtain conclusive results. In contrast, when the qPCR methods were used, success rates exceeding 99% were achieved with a single test. Additionally, all qPCR-based methods determined mouse genotypes by analysis of stool samples, highlighting the applicability of these methods for non-invasive genotyping. Loss of heterozygosity in the Apc gene in intestinal polyps was detected using the dual-probe assay with delta cycle threshold method. In summary, this study successfully implemented intercalator-based and probe-based qPCR methods, with and without professional analytical modules, for characterising Apc in tissue and stool samples. Furthermore, these methods can be extended to allow genotyping of other SNVs and can facilitate non-invasive genotyping of transgenic animals.